Hubungan Derajat Keparahan Stroke Dengan Kejadian Pneumonia Pada Pasien Post-Stroke Iskemik Akut - Wulandari, Eksy Andhika; Suroto, .; Hartono, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Pneumonia is one of the complications which is undergone the most in stroke patient. One of the factors which is related to pneumonia is the severity stroke. This research is to find out correlation between the severity of stroke and pneumonia. Method: This research is cross-sectional study. The research is conducted in the ward of Anggrek 2 Dr. Moewardi Hospital. The independent variable of this research is the severity ofÂ stroke, meanwhile the dependent variable is the pneumonia diagnosis. The severity of patient hospitalized in April until October 2013 is measured by NIHSS. The samples are taken in simple random sampling to the number of 64 samples, divided into 2 groups where each of them consists of 32 samples. The samples are divided into 2 groups based on the NIHSS score, such as mild ischemic stroke patient (score <15) and severe ischemic stroke patient (score >15). Pneumonia diagnosis is gained through the data from medical record at the sample taking. The data is analyzed by Chi Square to find out the significance statistically. Result: This research shows the result oftest is OR = 3,857; CI 95% 1,334â11,157. Patients with severe stroke have 3,857 more risk to have pneumonia than patients with mild stroke. Conclusion: There is a correlation between severity of stroke and pneumonia in patient with post-acute ischemic strokeÂ in Unit Penyakit Saraf Dr. Moewardi Hospital. Keyword: severity of stroke, pneumonia, NIHSSÂ